Digital precompensation of imperfections in quadrature modulators. - Marchesani, R. (IEEE Transactions on communications)
Residual carrier, balance, and quadrature error imperfections that are normally present in phase/quadrature modulators limit the use of direct modulation techniques in some applications. The classical precompensation techniques are revised and an adaptive solution proposed that improves performance by some order of magnitude